Excess capacity and efficiency in the quota managed Tasmanian Rock Lobster Fishery. (February 2017) - Rust, Steven; Yamazaki, Satoshi; Jennings, Sarah; Emery, Timothy; Gardner, Caleb
Abstract: Excess capacity is a major concern for fisheries management worldwide. It is often argued that Individual Transferable Quota (ITQ) systems will enhance efficiency and alleviate problems of excess capacity. While improvements in efficiency have been observed, most empirical studies have found only modest changes in excess capacity as a result of such systems. Using a database of compulsory log-book information for the Tasmanian Rock Lobster Fishery in Australia, from January 2000 to December 2013, this study presents the first analysis to investigate the dynamic behaviour of both excess capacity and efficiency (i.e. technical and scale efficiency) in an industrialised fleet after the introduction of quota management. The analysis revealed weak evidence for a prolonged adjustment in the fishery following the introduction of an ITQ system. In addition, no marked changes in excess capacity were observed over the study period; and furthermore, there was no evidence for an increase in excess capacity during a period of non-binding Total Allowable Catch (TAC) when race to fish behaviour increased in the fishery. The results suggest a limited ability of the ITQ system to alleviate levels of excess capacity in fisheries in the long-term. Highlights: Studied the dynamic behaviour of excess capacity and efficiency in an ITQ fishery. Data Envelopment Analysis was applied to log-book data from 2000 to 2013. Weak evidence for prolonged adjustment of the fishery after the ITQ was introduced. Consistently high level of excess capacity and low level of technical efficiency. No evidence for an increase in excess capacity when the TAC was non-binding.